2017
DOI: 10.1111/jace.14960
|View full text |Cite
|
Sign up to set email alerts
|

Improved dielectric properties in A′‐site nickel‐doped CaCu3Ti4O12 ceramics

Abstract: The improved dielectric properties and voltage‐current nonlinearity of nickel‐doped CaCu3Ti4O12 (CCNTO) ceramics prepared by solid‐state reaction were investigated. The approach of A′‐site Ni doping resulted in improved dielectric properties in the CaCu3Ti4O12 (CCTO) system, with a dielectric constant ε′≈1.51×105 and dielectric loss tanδ≈0.051 found for the sample with a Ni doping of 20% (CCNTO20) at room temperature and 1 kHz. The X‐ray photoelectron spectroscopy (XPS) analysis of the CCTO and the specimen wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Nickel doped CCTO were prepared and studied by Senda et al, [72] Wang et al, [73] Boonlakhorn et al [74] and Sun et al [9] In the aim of increasing the relative permittivity and decreasing the dielectric loss of CCTO, Sun et al [9] prepared CaCu 3À x Ni x Ti 4 O 12 (x = 0, 0.05, 0.1, 0.2) powders by the sol-gel method. The pellets were sintered at 1000-1060°C for 8 h. A very low tanδ value~0.025 was found at the CaCu 2.…”
Section: Doping Of Ccto By One Elementmentioning
confidence: 99%
See 4 more Smart Citations
“…Nickel doped CCTO were prepared and studied by Senda et al, [72] Wang et al, [73] Boonlakhorn et al [74] and Sun et al [9] In the aim of increasing the relative permittivity and decreasing the dielectric loss of CCTO, Sun et al [9] prepared CaCu 3À x Ni x Ti 4 O 12 (x = 0, 0.05, 0.1, 0.2) powders by the sol-gel method. The pellets were sintered at 1000-1060°C for 8 h. A very low tanδ value~0.025 was found at the CaCu 2.…”
Section: Doping Of Ccto By One Elementmentioning
confidence: 99%
“…Wang et al . showed that the doping of CCTO by 5 % of Co improved the dielectric properties and gave dielectric constant ϵ′≈7.4×10 4 and dielectric loss tanδ≈0.034 at room temperature and 1 KHz.…”
Section: Doping Of Cctomentioning
confidence: 99%
See 3 more Smart Citations